1999
DOI: 10.1016/s0893-133x(98)00063-3
|View full text |Cite
|
Sign up to set email alerts
|

Proton Magnetic Resonance Spectroscopy in the Frontal and Temporal Lobes of Neuroleptic Naive Patients with Schizophrenia

Abstract: Studies with proton magnetic resonance spectroscopy (MRS) have reported abnormalities in N-acetyl-aspartate (NAA), amino acids (AA) and choline (Cho) to creatine (Cr) ratios associated with schizophrenia. We report data on the three ratios in a sample of 18 neuroleptic naive patients with first-episode schizophrenia (eight studied in the dorsolateral prefrontal and 10 in the midtemporal lobe) and 24 healthy controls (14 studied in prefrontal and 10 in midtemporal lobes). Frontal lobe proton spectra were acquir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
41
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 95 publications
(45 citation statements)
references
References 49 publications
4
41
0
Order By: Relevance
“…The alterations most often found in the overall comparison of patients with healthy volunteers were a decrease of the NAA/Cr ratio [17][18][23][24][25][26][27][28][29] and of the NAA absolute value 19,30,31 . Regarding subgroup comparisons, Heimberg et al 32 , Bustillo et al 33 and Ende et al 34 found NAA differences between schizophrenics treated with atypical anti-psychotics as compared to schizophrenics under typical neuroleptics, and between each subgroup and its control.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The alterations most often found in the overall comparison of patients with healthy volunteers were a decrease of the NAA/Cr ratio [17][18][23][24][25][26][27][28][29] and of the NAA absolute value 19,30,31 . Regarding subgroup comparisons, Heimberg et al 32 , Bustillo et al 33 and Ende et al 34 found NAA differences between schizophrenics treated with atypical anti-psychotics as compared to schizophrenics under typical neuroleptics, and between each subgroup and its control.…”
Section: Resultsmentioning
confidence: 99%
“…Three of them used schizophrenic patients under no medication and, two of the studies were longitudinal. Cecil et al 25 and Choe et al 17 studied non-medicated patients and found NAA/Cr decrease. However, Bartha et al 42 did not find any NAA alteration in non-medicated schizophrenics.…”
Section: Medicationmentioning
confidence: 99%
See 2 more Smart Citations
“…A decrease (22%) in creatine kinase activity was found in schizophrenia (3), an enzyme critical for maintaining stable adenosine triphosphate (ATP) levels during altered neuronal activity (3, 17, 18). Other MRS studies in medication naïve patients suggest that decreases in the availability of high-energy phosphates may be a core feature of the illness (19-21). …”
Section: Introductionmentioning
confidence: 99%